Figure 3 from: Pujana RR, Wilf P, Gandolfo MA (2020) Conifer wood assemblage dominated by Podocarpaceae, early Eocene of Laguna del Hunco, central Argentinean Patagonia. PhytoKeys 156: 81-102. https://doi.org/10.3897/phytokeys.156.54175 - Pujana, Roberto R.; Wilf, Peter; Gandolfo, Maria A. (Zenodo, 2020)
Figure 3 Phyllocladoxylon antarcticum: A Growth rings of type D (TS), MPEF-Pb 10747 B detail of a growth ring of type D boundary (TS), MPEF-Pb 10776 C detail of roundish tracheids (TS), MPEF-Pb 10765 D opposite contiguous biseriate intertracheary radial pits (arrowheads) (RLS), MPEF-Pb 10767 E uniseriate non contiguous intertracheary radial pits (scanning electron microscope, SEM), MPEF-Pb 10776 F uniseriate contiguous (arrowheads) and non contiguous intertracheary radial pits (SEM), MPEF-Pb 10776 G cross-fields with large simple pits (RLS), MPEF-Pb 10707 H cross-fields with large pointed and narrow-bordered pits (RLS), MPEF-Pb 10765 I cross-fields with large simple pits (SEM), MPEF-Pb 10710 J wall alteration of the secondary walls of tracheids (RLS), MPEF-Pb 10767 K uniseriate rays (TLS), MPEF-Pb 10767 L uniseriate rays (TLS), MPEF-Pb 10747. Scale bars: 5 mm (A); 200 μm (B, K); 100 μm (C, L); 50 μm (D, F, G, H, I, J); 20 μm (E).